Primary true enterolithiasis: A rare cause of acute small bowel obstruction - Abdelhamid Jadib, MD; Houria Tabakh, MD; Lamiaa Chahidi El Ouazzani, MD; Keltoum Boumlik, MD; Romaissaa Boutachali, MD; Abdellatif Siwane, MD; Najwa Touil, MD; Omar Kacimi, MD; Nabil Chikhaoui, MD (Radiology Case Reports, 2022)
Enterolithiasis is an uncommon medical condition. It's defined by the formation of gastrointestinal concretion in the setting of intestinal stasis. Enteroliths are typically incidentally discovered during imaging and are a rare cause of acute small bowel obstruction. We report the case of acute small bowel obstruction, secondary to primary true enterolithiasis, in a 73-year-old male, with unremarkable medical history. He presented with clinical features in keeping with acute small bowel obstruction, for 2 days. An abdominal contrast-enhanced CT scan suggested a small bowel obstruction caused by a 32mm diameter enterolith located in the terminal ileum. The surgical management was successful and consisted of the removal of the enterolith after enterotomy.